(untitled) - Sedliak, Marian; Sulgan, Marian (Doprava a spoje, 2011)
The paper deals with the sequential supply of automobile manufacturers. It describes the main reasons for sequencing, used approaches, methods and the basic requirements for information systems providing the process of sequencing.